Understanding the Language Skills of a 19-Year-Old Individual with Down Syndrome: A Psycholinguistics Case - Rossy Halimatun Rosyidah (University of Surakarta, 2024)
ABSTRACT Language and speech ability of people with Down syndrome is usually slow; Down syndrome is more capable of being a receiver than an expresser in communication. This study aimed to explore the language skills of individuals with Down syndrome and to investigate how psycholinguistic approaches contribute to understanding the language ability of individuals with Down syndrome. The research method was qualitative and a case study with a single subject. The data were collected through observations and interviews. The analysis of the data consists of data transcribing, coding, and data categorization. The results showed a psycholinguistics approach can determine the language skills of a 19-year-old person with Down syndrome. The subject was able to understand simple everyday questions but she faced difficulties in answering questions related to pictures and multiple-choice questions, due to limited cognitive processes, lexicon, syntax, and phonology. Then the expressive and receptive abilities in language showed that the subject has quite good expressive abilities for the Down syndrome category, and for receptive abilities, the subject faced difficulty in complex, abstract questions, and also questions involving multiple choices.